Global cognitive function and processing speed are associated with gait and balance dysfunction in Parkinson's disease. Issue 1 (December 2016) - Pal, Gian; O'Keefe, Joan; Robertson-Dick, Erin; Bernard, Bryan; Anderson, Sharlet; Hall, Deborah
Abstract Background Our primary objective was to determine the relationship between global cognitive function and specific domains of gait and balance in a cohort of Parkinson's disease (PD) subjects. In a secondary analysis, we determined whether specific cognitive domains correlated with gait and balance performance. Methods Fourteen PD subjects (mean age 61.1 ± 7.8 years) were recruited from the Rush University Medical Center Movement Disorders clinic. Subjects underwent clinical assessment using the motor subsection of the Unified Parkinson's Disease Rating Scale (UPDRS) followed by quantitative gait and balance assessments using the APDM Mobility Lab™ system (Mobility Lab, APDM Inc., Portland, OR). Subjects completed global cognitive testing using the Mattis Dementia Rating Scale (MDRS) as well as domain specific cognitive measures. Spearman's rho was used to assess correlations between cognitive measures and gait and balance function, with False Discovery Rate (FDR) correction for multiple comparisons. Results Global cognitive function had the strongest correlation with stride velocity (r = 0.816, p = 0.001), turn duration (r = −0.806, p = 0.001), number of steps to turn (r = −0.830, p = 0.001), and mean velocity of postural sway in the medio-lateral direction (r = −0.726, p = 0.005). A significant correlation was found between processing speed and two turning measures (turn duration, r = −0.884, p = 0.001; number of steps to turn, r = −0.954, p < 0.001), but no other associations were found between specific cognitive domains and gait domains. Conclusions This pilot study provides preliminary data regarding the association between global cognitive function and pace-related measures of gait, turning, and postural sway. Furthermore, reduced processing speed was found to be associated with difficulty in performing turns.